Użycie strategii uczenia się gramatyki przez studentów filologii angielskiej - Pawlak, Mirosław (Neofilolog, 2019)
Grammar learning strategies can be defined as deliberate actions and thoughts which are employed for learning and gaining greater control over the use of grammar structures (Cohen and Pinilla-Herrera, 2009: 64). This indicates that they are used with the purpose of developing both ex-plicit and implicit second language knowledge. Surprisingly, empirical in-vestigations of such strategic devices are few and far between, with the available studies relying on different classifications and data collection tools, and often producing conflicting results. The present paper contrib-utes to this important line of inquiry by reporting the findings of a re-search project which aimed to explore the use of these strategies by 200 advanced adult learners of English, future teachers of this language en-rolled in a BA program in English philology. The data were collected by means of an instrument designed by the present author (Pawlak, 2009c, 2010, 2011) on the basis of his taxonomy of such strategic devices and, similarly to earlier studies in this area (e.g. Pawlak 2008, 2009a), the analy-sis showed that the choice of grammar learning strategies hinges upon a number of variables and there are differences between the responses to Likert scale items and open-ended questions. The results serve as a basis for tentative suggestions for grammar instruction in modern languages departments and directions for future research.